Metformin increases pressure pain threshold in lean women with polycystic ovary syndrome - Kiałka M; Milewicz T; Sztefko K; Rogatko I; Majewska R (Dove Medical Press, 2016)
Marta Kiałka,1 Tomasz Milewicz,1 Krystyna Sztefko,2 Iwona Rogatko,2 Renata Majewska3 1Department of Gynecological Endocrinology, Jagiellonian University, Medical College, Kraków, Poland; 2Department of Clinical Biochemistry, Jagiellonian University, Medical College, Kraków, Poland; 3Department of Epidemiology, Chair of Epidemiology and Preventive Medicine, Jagiellonian University Medical College, Kraków, Poland Background: Despite the strong preclinical rationale, there are only very few data considering the utility of metformin as a potential pain therapeutic in humans. The aim of this study was to determine the association between metformin therapy and pressure pain threshold (PPT) in lean women with polycystic ovary syndrome (PCOS). We hypothesized that metformin therapy in lean PCOS women increases PPT. Materials and methods: Twenty-seven lean PCOS women with free androgen index phenotype >5 and 18 lean healthy controls were enrolled in the study. Fifteen of the PCOS women were randomly assigned to be treated with metformin 1,500 mg daily for 6 months. PPT and plasma β-endorphin levels were measured in all women at the beginning of the study and after 6 months of observation. Results: We observed an increase in PPT values measured on deltoid and trapezius muscle in the PCOS with metformin group after 6 months of metformin administration (4.81±0.88 kg/cm², P<0.001 on deltoid muscle, and 5.71±1.16 kg/cm² on trapezius muscle). We did not observe any significant changes in PPT values in the PCOS without treatment group and in controls. We did not observe any significant changes in serum β-endorphin levels in any studied groups during the 6-month observation. Conclusion: We conclude that metformin therapy increases PPT in lean PCOS women, without affecting plasma β-endorphin concentration. Our results may suggest the potential role of metformin in pain therapy. We propose that larger, randomized studies on metformin impact on pain perception should be performed. Keywords: metformin, pressure pain threshold, pressure algometry, polycystic ovary syndrome, pain therapy